(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2023)
This article explores the development of speech competence through interdisciplinary communication. Speech competence is a crucial skill that enables effective communication and understanding in various contexts. The article discusses the significance of interdisciplinary communication in enhancing speech competence, as it involves the collaboration and exchange of ideas across different disciplines. It further investigates the benefits and challenges associated with interdisciplinary communication for the development of speech competence. The findings highlight the importance of promoting interdisciplinary collaboration to foster effective communication skills and enhance speech competence in individuals.